A year in the life of Downton Abbey - Fellowes, Jessica (St Martin's Press, 2014)
It's 1924 and there have been many changes at Downton Abbey since the family and their servants first welcomed us there twelve years ago. A generation of men has been tragically lost in the Great War; children are once again breathing new life into the great house; a chauffeur now sits at the Grantham dinner table; and skirt hems continue to rise. Still, many things at Downton remain largely unchanged. Nanny still holds sway in the nursery, and there are still fetes to be organized, menus to be planned, and farms to be run. This book, packed full of new photographs, explores the seasonal events and celebrations of the great estate, with a delicious array of traditional British recipes adapted for modern kitchens.--From publisher description.